The offices of the U.S. president as policy tools - Chris Pepin-Neff; William McManus; Ben Ormerod (Cogent Social Sciences)
White House spaces and offices are not created equal. The spaces that constitute the offices of the president are distinctive, familiar, and publicly translatable assets of statecraft. Whether in the Oval Office, the Treaty Room, aboard Air Force One, or even in the Rose Garden their use is designed to deliver information and send an influential signal to the public. Many of the offices of the president have their own cognitive profiles in the public’s mind. The utilization of physical spaces establishes a repertoire of routine and ritual that informs the public about how important a potential policy issue is. The question driving this research asks: How do the physical offices of the president function as policy instruments? We argue that physical offices can be considered policy tools under categories of (1) nodality, when they are employed as a tool to publicly rally around a policy decision and (2) authority, when they serve as a heuristic regarding command-and-control to the public. In short, the physical offices of the president facilitate policy adoption by serving as devices to communicate information about the direction and gravity of a policy decision.